Конструювання змісту формування медіакомпетентності майбутніх лікарів доклінічної професійної підготовки в медичному університет - Мурзіна, Олена Анатоліївна; Murzina, O. A. (My University, 2025)
У статті розкрито важливість конструювання змісту формування медіакомпетентності майбутніх лікарів у процесі доклінічної професійної підготовки в медичному університеті. При формуванні медіакомпетентності майбутніх лікарів у процесі доклінічної професійної підготовки нами враховано особливості освітньо-професійної програми та навчальних планів, зокрема їх мета і завдання, а також структуру медіакомпетентності лікаря, яка має сформуватися на відповідному етапі. Важливого значення для засвоєння змісту навчальних дисциплін, набуття практичних навичок на доклінічному етапі має оволодіння медіакомпетентністю, оскільки це дає змогу майбутнім лікарям застосовувати медіазасоби у навчанні та в майбутній професійній діяльності, орієнтуватися в медичному медіапросторі. З іншого боку, на етапі доклінічної професійної підготовки можливе застосовування додаткових курсів, удосконалення матеріалів навчальних дисциплін, що сприяло б формуванню медіакомпетентності. Тому навчальні плани підготовки лікарів структуровані з урахуванням бажаного результату навчання – формуванню медіакомпетнтності. В освітньо-професійній програмі в медичних університетах, зокрема на етапі доклінічної професійної підготовки, має бути закладена система медіакомпетентності, яка необхідна для ефективного виконання професійних обов’язків лікарем відповідної спеціальності в сучасних умовах. Задля цього переглянуто зміст підготовки майбутнього спеціаліста, адже формування медіакомпетентності потребує міждисциплінарної інтеграції знань. The article reveals the importance of constructing the content of the formation of media competence of future doctors in the process of preclinical professional training at a medical university. When forming the media competence of future doctors in the process of preclinical professional training we take into account the peculiar features of the educational and professional program and curricula, their goals and objectives in particular, as well as the structure of the doctor’s media competence that should be formed at the appropriate stage. Mastering media competence is of great importance for acquiring the content of academic disciplines and overtaking practical skills at the preclinical stage since it allows future doctors to use media tools in training and in future professional activities, to navigate in the medical media space. On the other hand, it is possible to choose additional courses, improve the materials of academic disciplines at the stage of preclinical professional training that would contribute to the formation of media competence. Therefore, the curricula of doctors’ training are structured taking into account the desired outcome of learning – the formation of media competence. The educational and professional program in medical universities, at the stage of preclinical professional training in particular, should include a system of media competence which is necessary for the effective performance of professional duties by a doctor of the relevant specialty in modern conditions. For this purpose the content of the training of a future specialist has been revised since the formation of media competence requires interdisciplinary integration of knowledge. When restructuring the curricula at the stage of preclinical professional training in medical universities, we have identified sections that should contribute to the formation of media competence of future doctors and, accordingly, integrate knowledge from various academic disciplines.
Construction of the content of formation of media competence of future doctors in the process of preclinical professional training at a medical university
Keywords: медіакомпетентність; доклінічна професійна підготовка; зміст освітнього процесу; медіапростір; медіапродукт; media competence; preclinical professional training; content of the educational process; media space; media product